2018
DOI: 10.1155/2018/7973519
|View full text |Cite
|
Sign up to set email alerts
|

Building Resilience to Climate Change: Pilot Evaluation of the Impact of India’s First Heat Action Plan on All-Cause Mortality

Abstract: Background Ahmedabad implemented South Asia's first heat action plan (HAP) after a 2010 heatwave. This study evaluates the HAP's impact on all-cause mortality in 2014–2015 relative to a 2007–2010 baseline. Methods We analyzed daily maximum temperature (Tmax)-mortality relationships before and after HAP. We estimated rate ratios (RRs) for daily mortality using distributed lag nonlinear models and mortality incidence rates (IRs) for HAP warning days, comparing pre- and post-HAP periods, and calculated incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…While most common in North America and Europe, major cities in China and a growing number of cities in India have implemented early-warning systems that notify residents of poor air quality and alert health professionals to prepare for air pollution-related hospitalizations. In 2014, Ahmedabad, India, was the first city in South Asia to implement a heatwave early warning system [122], with preliminary evidence indicating lower summertime mortality rates after its implementation and larger declines at the highest temperatures [123].…”
Section: The Role Of Cities In Mitigating Pollution and Related Cvd Bmentioning
confidence: 99%
“…While most common in North America and Europe, major cities in China and a growing number of cities in India have implemented early-warning systems that notify residents of poor air quality and alert health professionals to prepare for air pollution-related hospitalizations. In 2014, Ahmedabad, India, was the first city in South Asia to implement a heatwave early warning system [122], with preliminary evidence indicating lower summertime mortality rates after its implementation and larger declines at the highest temperatures [123].…”
Section: The Role Of Cities In Mitigating Pollution and Related Cvd Bmentioning
confidence: 99%
“…Higher ozone and additional warming in the mitigation scenario may reduce crop productivity 21 ; however, this may be partially compensated by a lower ambient PM 2.5 that also has a negative association with productivity 22 . The additional warming may enhance heat stress condition; however, this can be tackled by an effective heat management plan that has been proven to save lives in India 23 . Quantifying such impact for the two emission pathways is beyond the scope of this work and will be reported separately.…”
Section: Discussionmentioning
confidence: 99%
“…The initial result returned 51 sources. After reviewing these sources manually, it became evident that the articles by Hess et al [8], Knowlton et al [14], and Azhar et al [32], with overlapping authorship, are the main data sources, based on which the appraisals of the HAP were made.…”
Section: Methodsmentioning
confidence: 99%
“…A pilot evaluation of the HAP conducted by Hess et al [8] suggested that the HAP may be effective in addressing heat vulnerability in disadvantaged communities in crowded cities. Drawing on epidemiological evidence, their research evaluated the impacts of the HAP on all-cause mortality in 2014-2015, relative to a baseline from 2007-2010.…”
Section: Acclaimed Impactsmentioning
confidence: 99%
See 1 more Smart Citation